Pengaruh Citra Merek, Harga dan Kualitas Produk Terhadap Keputusan Pembelian Produk Iphone (Studi Kasus Mahasiswa FEB Universitas Islam Malang Angkatan 2019) - Muhammad Choirul Miqdad; Muhammad Mansur; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Technological developments in the current era are very advanced, almost all people's lives depend on information technology. Advances in information technology encourage people to always use it to meet their needs. One of the technologies that is currently growing rapidly is the smartphone. Advances in technology have made companies compete to create competitive smartphone products in the market. One of them is the iPhone. The iPhone was the first mobile phone made by Apple to hit the market in 2007. The iPhone tried to come out differently in terms of price and product quality. The iPhone now has a distinctive brand image by using an information system that is different from other smartphones. The purpose of this study was to determine and analyze the influence of brand image, price, product quality partially on the purchase decision of iPhone products. The population in this study were Students of the Faculty of Economics and Business, Islamic University of Malang Class of 2019 who have iPhone smartphones. The approach method uses a non-probability sampling technique, namely purposive sampling which is a sample collection technique based on certain criteria using a questionnaire distributed to 85 respondents and using the SPSS analysis tool. The results of this study indicate that partially price and product quality have a significant positive effect on purchasing decisions. Meanwhile, brand image has a significant negative effect on purchasing decisions for iPhone products. Keywords: Brand Image, Price, Product Quality, Purchase Decision